Balsių asimiliacijos ypatumai Akmenės šnektoje - Murinienė, Lina (Kalbotyra, 1995)
The article deals with the peculiarities of vowel assimilation characteristic of an eastern dialect of North Žemaitian. The dialect investigation focuses on its center - Akmenė, and principal points: Papilė, Sablauskiai, Alkiškiai, Kivyliai, Klykoliai, Vegeriai. This is a typical Žemaitian dialect closely related to that of Tirkšliai. The characteristic features of the Akmenė dialect vocalism are as follows: 1) the vowel (most of all the e) assimilation is especially regular; 2) the e vowel before closed vowels is assimilated regardless of the stress position; 3) according to the rise-level of the tongue it is inclined to coordinate the articulation of all the vowels in the word. The above area is sometimes treated as an exclusive edge of the said dialect with characteristic vocalism which cannot be found in other North Žemaitian dialects. This sort of suggestion might have been included because of the existing assimilation rules of Latvian (in particular the north-east part of the dialect). Besides, the forms with closed ẹ supplant the natural Žemaitian forms and consolidate throughout the entire paradigm.